Cardiovascular disease risk assessment for Aboriginal and Torres Strait Islander adults aged under 35 years: a consensus statement. Issue 9 (15th March 2020) - Agostino, Jason W; Wong, Deborah; Paige, Ellie; Wade, Vicki; Connell, Cia; Davey, Maureen E; Peiris, David P; Fitzsimmons, Dana; Burgess, C Paul; Mahoney, Ray; Lonsdale, Emma; Fernando, Peter; et al.
Summary: Cardiovascular disease (CVD) is a leading cause of preventable morbidity and mortality in Aboriginal and Torres Strait Islander peoples. This statement from the Australian Chronic Disease Prevention Alliance, the Royal Australian College of General Practitioners, the National Aboriginal Community Controlled Health Organisation and the Editorial Committee for Remote Primary Health Care Manuals communicates the latest consensus advice of guideline developers, aligning recommendations on the age to commence Aboriginal and Torres Strait Islander CVD risk assessment across three guidelines. Main recommendations: In Aboriginal and Torres Strait Islander peoples without existing CVD: CVD risk factor screening should commence from the age of 18 years at the latest, including for blood glucose level or glycated haemoglobin, estimated glomerular filtration rate, serum lipids, urine albumin to creatinine ratio, and other risk factors such as blood pressure, history of familial hypercholesterolaemia, and smoking status. Individuals aged 18–29 years with the following clinical conditions are automatically conferred high CVD risk: ▶ type 2 diabetes and microalbuminuria; ▶ moderate to severe chronic kidney disease; ▶ systolic blood pressure ≥ 180 mmHg or diastolic blood pressure ≥ 110 mmHg; ▶ familial hypercholesterolaemia; or ▶ serum total cholesterol > 7.5 mmol/L. Assessment using the National Vascular Disease Prevention Alliance absolute CVD risk algorithm should commence from the age of 30 years at the latest — consider upward adjustment of calculated CVD risk score, accounting for local guideline use, risk factor and CVD epidemiology, and clinical discretion. Assessment should occur as part of an annual health check or opportunistically. Subsequent review should be conducted according to level of risk. Changes in management as a result of this statement: From age 18 years (at the latest), Aboriginal and Torres Strait Islander adults should undergo CVD risk factor screening, and from age 30 years (at the latest), they should undergo absolute CVD risk assessment using the NVDPA risk algorithm.